Powerful Women: Does Exposure Reduce Bias?* - Beaman, Lori; Chattopadhyay, Raghabendra; Duflo, Esther; Pande, Rohini; Topalova, Petia (Quarterly Journal of Economics, 2009)
We exploit random assignment of gender quotas for leadership positions on Indian village councils to show that prior exposure to a female leader is associated with electoral gains for women. After ten years of quotas, women are more likely to stand for, and win, elected positions in councils required to have a female chief councilor in the previous two elections. We provide experimental and survey evidence on one channel of influence—changes in voter attitudes. Prior exposure to a female chief councilor improves perceptions of female leader effectiveness and weakens stereotypes about gender roles in the public and domestic spheres.